Household as a Participant of an Innovation Ecosystem - Glukhov, Vladimir Vladimirovich; Lialina, Zhanna Ivanovna; Rozhkov, Yuri Vladimirovich; Vasiukova, Liudmila Konstantinovna; Kosolapov, Alexander Borisovich (International Review of Management and Marketing, 2016)
The article shows the results of the investigation in which a household is described as a participant of an ecosystem. A household has appropriate properties that can be considered from both biological and economic point of view. The importance of raising children as future innovators using the techniques of psycho-diagnostics and the abilities of combinatorial economics is demonstrated in the paper. Besides, a hypothesis is provided about the necessity of wider application of analogies with ecology to develop the theory of innovation risks in a household. Household is shown as an ecosystem in which the change of one component condition causes the change in the condition of the other. Analysis of a household as an ecosystem has been insufficiently investigated yet. Its social, economic and environmental components have not been clearly defined and are considerable opportunity for studying using the system approach and the impact on the surrounding society. Keywords: family household, ecosystem, innovation ecosystem, social-ecosystems, analogy, risks. JEL Classifications: R20, R29, Q16, Q56.